Ultra-High Performance ’Ductile’ Concrete Technology Toward Sustainable Construction - Voo, Yen Lei (International Journal of Sustainable Construction Engineering and Technology, 2011)
This paper briefly presents an overview of the material characteristics of a Malaysia blend of ultra-high performance ductile concrete (UHPdC) know as DURA®. Examples of the environmental impact calculations of UHPdC structures compared to that of conventional reinforced concrete design are presented. The comparison studies show that many structures constructed from UHPdC are generally more environmentally sustainable than built of the conventional reinforced concrete with respect to the reduction of CO2 emissions and embodied energy. The enhanced durability of UHPdC also provides for significant improvements in the design life, which further supporting the concept of sustainable construction.